Avaliação da qualidade de vida de pessoas com estomias intestinais e disposições associativas - COSTA , Silvana Mendes (2023)
Having an ostomy greatly impacts the person's quality of life, given the numerous changes it takes, whether physical or psychological, thus giving the person the opportunity to face challenges in their daily lives. This study aimed to evaluate the quality of life of people with anintestinal ostomy and associative dispositions registered in São Luís - MA. This is a cross-sectional, descriptive and correlational study with a quantitative approach. The sample consisted of 154 people with intestinal stomas, of the colostomy and ileostomy type, registered at the Orthosis and Prosthesis Service of the Municipal Health Department of São Luís Maranhão, aged 18 years or more and with ostomy made at least 6 months ago. Three questionnaires were used for data collection with socio-demographic, clinical and quality of life data, this specific questionnaire for assessing the quality of life of ostomy patients, a translated, adapted and validated questionnaire for the Portuguese language, City OF Hope- Quality OF Life- Ostomy (COH-QOL-OQ), consisting of 43 items divided into the domains of physical, psychological, spiritual and social well-being, arranged on a Likert scale. In this research, therewas a predominance of males (62.6%); 50.0% reported having partners; resided in São Luís (55.5%) and identified themselves as brown (61.3%). Of the interviewees, 77 (49.7%) said they were Catholic (94.2% practiced the religion), had their own house (94.8%), and 71.6% stoppedworking after making the ostomy. Monthly income ranged from less than one minimum wage (41.9%) to 2 minimum wages (41.3%). The most prevalent type of ostomy was the colostomy (81.2%), with the length of stay defined as temporary (60.4%). As a cause, cancer was identified as the most prevalent (47.4%). Among the sample, 52% denied complications resulting from the ostomy. Among those analyzed, 64.3% said they had extra expenses resulting from the ostomy. As for the quality of life variables, spiritual well-being stands out with the highest average among the participants, 8.45. Physical well-being had an average of 4.05 on a reverse scale (being considered positive for better quality of life), followed by psychological (5.85) and social (6.33) factors. Thus, the association between sociodemographic and clinical factors and quality of life was statistically significant (p-value < 0.05) for religion, education, type of household, household characteristics, number of residents,permanence of the stoma, incidence of complications; post-stomy work, presence of spouse, practice of physical activities and difficulties in accessing health services. Furthermore, there was a high significance of the cause of the ostomy for several domains, such as physical (p- value = 0.03), psychological (p-value = 0.01), social (p-value = 0.01) and overall (p value = 0.05). Similarly, work activity and social and/or family support network were the variables withthe highest correlation coefficients (p-value < 0.03). In this sense, Nursing has a primordial role in this care, that is, knowing the factors that influence the better quality of life of people with a stoma, enables planning for a holistic, humanized and quality assistance, since the nurse is the communication link between people ostomy patient, team and family members.